Study of seawater intrusion in the coastal alluvial aquifer, West Semarang, Central Java, Indonesia - Fajrianto, Rizq; Wilopo, Wahyu; Pranantya, Pulung Arya; Laowattanabandit, Pipat (Brawijaya University, 2026)
Seawater intrusion occurs when seawater enters aquifer systems, which happens a lot in coastal areas. The coastal zone of Tugu District, Semarang City, Central Java Province, is one such area where groundwater becomes increasingly vulnerable due to intensified pumping and land-use changes near the shoreline. This study aimed to ascertain the incidence of seawater intrusion in the western coastal region of Semarang and to examine its characteristics and sources using an integrated geological, hydrogeological, geophysical, groundwater geochemical, and stable-isotope analysis approach. A descriptive quantitative method was employed, including the measurement of 59 geological/hydrogeological sites, four geoelectrical soundings, and the acquisition of 14 groundwater samples from wells and springs. The parameters examined encompassed physical properties (EC, TDS, pH), chemical composition (Cl?, Na?/Cl? ratio, Cl?/SO?²? ratio, Simpson index, and BEX), facies classifications using Piper diagrams, and stable isotope ratios (?¹?O and ?²H). The results showed that several locations, especially along the coast of Mojorejo and Mangkang Wetan Villages, had EC values exceeding 10,000 µS/cm and Cl? concentrations above 4,000 mg/L. Chemical ratios suggested that salinization processes are still active. Piper diagrams indicated that alkali-chloride type predominated in coastal areas. Isotope analysis showed that groundwater and seawater mixed. These findings demonstrated that the effects of intrusion have damaged shallow aquifers in the alluvial region. Managing coastal groundwater requires the stringent implementation of conservation zones, restrictions on borehole extraction, and the use of geoindicators for monitoring. A multidisciplinary approach remains essential for fully understanding seawater-intrusion dynamics in tropical coastal environments.